Hyaluronic acid—dexamethasone nanoparticles for local adjunct therapy of lung inflammation - Cámara, Candelaria Inés (2021)
The delivery of a dexamethasone formulation directly into the lung appears as an appro-priate strategy to strengthen the systemic administration, reducing the dosage in the treatment of lung severe inflammations. For this purpose, a hyaluronic acid-dexamethasone formulation was developed, affording an inhalable reconstituted nanosuspension suitable to be aerosolized. The physico-chemical and biopharmaceutical properties of the formulation were tested: size, stability, loading of the spray-dried dry powder, reconstitution capability upon redispersion in aqueous me-dia. Detailed structural insights on nanoparticles after reconstitution were obtained by light and X-ray scattering techniques. (1) The size of the nanoparticles, around 200 nm, is in the proper range for a possible engulfment by macrophages. (2) Their structure is of the core-shell type, hosting dex-amethasone nanocrystals inside and carrying hyaluronic acid chains on the surface. This specific structure allows for nanosuspension stability and provides nanoparticles with muco-inert proper-ties. (3) The nanosuspension can be efficiently aerosolized, allowing for a high drug fraction poten-tially reaching the deep lung. Thus, this formulation represents a promising tool for the lung administration via nebulization directly in the pipe of ventilators, to be used as such or as adjunct therapy for severe lung inflammation.